Effect of Use Hormonal Progestin Birth Control on Length of Use, Incidence of Menstrual Cycle Disorders in Birth Control Acceptors in Muara Enim District in 2024 - Olivia Nency; Desiani Putri Utami; Desna Pramita Devi; Laila Farhan; Meyta Sari; Mona Fitri; Neti; Rosdiana Juliani; Lidia Aryani Sapitri (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the effect of progestin hormonal contraceptive use on the duration of use and the incidence of menstrual cycle disorders among contraceptive acceptors in Muara Enim District in 2024. The method used is a correlational design with a cross-sectional approach. The population in this study consisted of all hormonal contraceptive acceptors in Muara Enim District, with a sample size of 853 people, determined using G Power software. Data analysis was conducted using the Spearman’s rho test. The statistical test results showed a p-value of 0.000 (<0.05), indicating a significant relationship between hormonal contraceptive use and menstrual cycle disorders. A correlation coefficient of 0.28 indicates a fairly strong and positive relationship. Furthermore, there is a relationship between the duration of hormonal contraceptive use and menstrual cycle disorders, with a p-value of 0.000 (<0.05) and a correlation coefficient of 0.39, suggesting a moderate and positive relationship in the same direction. These findings are expected to provide valuable information for healthcare providers to offer more accurate recommendations regarding potential menstrual cycle disorders in progestin hormonal contraceptive users, enabling patients to better understand the possible risks associated with this contraceptive method.